Dairy Farming in Southern Karnataka: An Economic Analysis under Varying Groundwater Regime - Sharif, Mahin (Indian Journal of Dairy Science, 2014)
The study encompassed computation of cost of milk production and analysis of milk production function of different species of milch animals under different levels of groundwater regimes (safe, semi-critical, critical and overexploitation). The study was conducted in the Chamarajanagar and Mysore districts of Karnataka state, which happen to represent both different groundwater regime and progressive dairy region. The study indicated noticeable variations in cost of milk production across species and regions. Cost of milk production was highest from local cows while it was least in crossbred cows. The net returns were highest for crossbreds while marginally Â negative net returns were observed in other cases. From the functional analysis, it was revealing that concentrates and dry fodder exerted their significant influence on milk production. Dummy coefficient used to reflect levels of groundwater exploitation on milk production, showed that there was an undesirable effect of groundwater exploitations on the milk production and performance of milch animals